Attitude and practice of family planning methods among Roma women living in northern Turkey - Ilknur Aydin Avci; Figen Cavusoglu; Mesiya Aydin; Birsen Altay (Elsevier, 2018)
Objective: This study aims to investigate the attitude and practice of family planning (FP) methods among Roma women living in northern Turkey. Methods: A total of 120 Roma women living in northern Turkey participated in this descriptive study. Data were collected using a questionnaire. The scale of FP attitude was used. Results: The mean age of participants was 28.9 ± 1.8. Among the participants, 37.5% (45/120) were primary school graduates, 70.8% (85/120) were unemployed, 73.4% (88/120) were in a consensual marriage and 94.2% (113/120) had children. The majority or 85.8% (103/120) of the participants stated that they used FP methods. Intrauterine device (57.4%, 69/120) and withdrawal method (22.3%, 27/120) were the most frequently used FP methods. Conclusions: The rates at which Roma women use FP were high. Their attitudes towards FP tended to be negative and the methods used were primarily related to females. Keywords: Attitude, Family planning, Roma women